2013
DOI: 10.3109/03639045.2013.838582
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of ketoconazole, itraconazole and voriconazole on the pharmacokinetics of imatinib and its main metabolite GCP74588 in rat

Abstract: The aim of the study was to develop a high performance liquid chromatography method for simultaneous determination of imatinib and CGP74588 in rat serum and study the inhibition effects of ketoconazole, itraconazole and voriconazole on pharmacokinetics of imatinib and CGP74588 in rats. In our study, we found that ketoconazole caused a significant increase (63.4%) in the AUC of imainib and a 28.8% increase in Cmax, which was greater than that of itraconazole but lower than that of voriconazole. When co-administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…co-administration group (p40.05), while there was statistical significance for MRT of imatinib (p50.01), when co-oral administration imatinib with dasatinib, MRT (0-t) decreased from 11.0 to 8.7 ng/mL of imatinib (p50.01), it indicated dasatinib could slightly induce the pharmacokinetics of imatinib. As for dasatinib (Table 2 and Figure 4b), the pharmacokinetic parameters of co-administration group compared with dasatinib group, C max increased from 113.4 to 446.2 ng/mL (p50.01), AUC (0-t) increased from 1012.3 to 3477.4 h ng/mL (p50.01), CL decreased from 15.2 to 4.0 L/h/kg (p50.01), V decreased from 118.2 to 26.9 L/kg (p50.01), while there was no statistical significance for t 1/2 and MRT of dasatinib between dasatinib group and co-imatinib is mainly metabolized by CYP3A4 and CYP3A5 in the liver 19 . Other isoenzymes, including CYP1A2, CYP2D6, CYP2C9 and CYP2C19, contribute to the metabolism of imatinib in a relatively minor extent 34 .…”
Section: Parameters Unitmentioning
confidence: 62%
See 1 more Smart Citation
“…co-administration group (p40.05), while there was statistical significance for MRT of imatinib (p50.01), when co-oral administration imatinib with dasatinib, MRT (0-t) decreased from 11.0 to 8.7 ng/mL of imatinib (p50.01), it indicated dasatinib could slightly induce the pharmacokinetics of imatinib. As for dasatinib (Table 2 and Figure 4b), the pharmacokinetic parameters of co-administration group compared with dasatinib group, C max increased from 113.4 to 446.2 ng/mL (p50.01), AUC (0-t) increased from 1012.3 to 3477.4 h ng/mL (p50.01), CL decreased from 15.2 to 4.0 L/h/kg (p50.01), V decreased from 118.2 to 26.9 L/kg (p50.01), while there was no statistical significance for t 1/2 and MRT of dasatinib between dasatinib group and co-imatinib is mainly metabolized by CYP3A4 and CYP3A5 in the liver 19 . Other isoenzymes, including CYP1A2, CYP2D6, CYP2C9 and CYP2C19, contribute to the metabolism of imatinib in a relatively minor extent 34 .…”
Section: Parameters Unitmentioning
confidence: 62%
“…Drug-drug interactions might be associated with serious or even fatal adverse events, or can lead to reduced therapeutic effects of either drug [15][16][17][18][19] . Interactions can be classified into those that are pharmacokinetic and those that are pharmacodynamic.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro study indicated that isavuconazole, ketoconazole, or voriconazole exhibited inhibitory effect on the metabolism of methadone in liver microsome both in human and rat. It has been reported that ketoconazole, itraconazole, and voriconazole could inhibit the metabolism of imatinib and carvedilol by effecting on CYP3A4 . Simultaneously, it has been reported that methadone is mainly metabolized through CYP3A4 .…”
Section: Discussionmentioning
confidence: 99%
“…In CML and GIST patients, the most serious fungal infection is invasive aspergillosis, which can lead to death 17. Co-administered IMA and VOR as one treatment protocol in those patients have been recognized, and the effect of VOR on the metabolism of IMA also has been studied in vivo18 and in vitro 19. However, to the best of our knowledge, there are currently no studies examining DDIs associated with the concurrent use of IMA and VOR, especially the effect of IMA on VOR metabolism.…”
Section: Introductionmentioning
confidence: 99%